PENERAPAN PENDEKATAN DEEP LEARNING DALAM PEMBELAJARAN EKONOMI PADA PROGRAM MAGANG KEPENDIDIKAN DI KELAS 12 IPS MAN 1 MERANGIN - Tiara Danliani Putri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The teaching internship program aims to provide students with direct experience in applying pedagogical and professional competencies in schools. This activity was carried out in Grade XII Social Sciences at MAN 1 Merangin, focusing on the implementation of the deep learning approach in Economics instruction, particularly on the topics of the Balance of Payments and International Trade. The deep learning approach was chosen to encourage students to understand concepts more deeply, connect the material with global economic phenomena, and develop critical thinking skills in analyzing data and real-world cases. This study employed a qualitative descriptive method with data collected through classroom observations, interviews with teachers and students, and documentation during the learning process. The results show that the application of deep learning—through activities such as analyzing Balance of Payments graphs, group discussions on factors affecting exports and imports, and case studies on international trade—successfully increased student engagement. Students were able to understand key components of the Balance of Payments, such as the current account and capital account, and relate these concepts to Indonesia’s economic conditions in the era of globalization. The deep learning approach proved effective in enhancing students’ conceptual understanding and analytical abilities on the topics of the Balance of Payments and International Trade. This approach can serve as an alternative instructional strategy to enrich the learning experience and improve the quality of Economics education at the senior high school level.